Advantages of Electro-deposited Gold on Carbon Electrodes for NT-proBNP Immunosensor for Development of Heart Failure Test Kit - Aiemderm, Pongsakorn; Monkhang, Kanchana; Wongjard, Sureeporn; Choowongkomon, Kiattawee; Mongkoldhumrongkul Swainson, Napachanok Mongkoldhumrongkul Swainson; Prasittichai, Chaiya; Kraiya, Charoenkwan (Applied Science and Engineering Progress, 2024)
Accurate measurement of the N-terminal pro B-type natriuretic peptide (NT-proBNP) in serum is important for the diagnosis of heart failure (HF). Carbon screen-printed electrodes (SPCEs) modified with graphene oxide (GO) or gold (Au) were compared for the construction of NT-proBNP immunosensors. NT-proBNP and its recognition unit, a single-chain variable fragment fused with alkaline phosphatase (scFv-AP), were expressed and purified. The currents of the electrodes immobilized with scFv-AP were measured after adding an ethanolamine (ETA), blank and NT-proBNP in either phosphate buffer saline (PBS) or human serum. SPCE/Au had lower mean baseline slopes than for SPCE/GO for all measurements, in both PBS and serum, indicating greater accuracy for SPCE/Au. None of the measurements in PBS had statistically different peak currents between SPCE/GO and SPCE/Au; however, there was a significant difference with the serum. The significant reduction of SPCE/ GO peak currents after applying serum blank implied non-specific absorption on the surface. The peak current of 300 pg/mL of NT-proBNP in the serum measured on SPCE/Au was significantly higher (by a factor of three) than on SPCE/GO, suggesting the possibility of using SPCE/Au to detect NT-proBNP at higher concentrations. The binding efficiency of scFv-AP to NT-proBNP did not depend on the electrodes, as shown by the similar delta peak-currents (Blank-Target). Thus, immobilized scFv-AP on SPCE/Au electrodes had good potential to accurately detect NT-proBNP in serum, for use in the fabrication of an HF test kit.